Novel combination therapy for platinum-eligible patients with locally advanced or metastatic urothelial carcinoma: a systematic review and network meta-analysis - Yanagisawa, Takafumi; Mori, Keiichiro; Matsukawa, Akihiro; Kawada, Tatsushi; Katayama, Satoshi; Laukhtina, Ekaterina; Rajwa, Pawel; Quhal, Fahad; Pradere, Benjamin; Fukuokaya, Wataru; Iwatani, Kosuke; Pichler, Renate; et al. (Cancer immunology, immunotherapy, 2025)
Recent phase 3 randomized controlled trials (RCTs) demonstrate the promising impact of immune checkpoint inhibitor (ICI)-based combination therapies on locally advanced or metastatic urothelial carcinoma (UC). However, comparative data on the efficacy and toxicity of different ICI-based combinations are lacking. This study aims to compare the efficacy of first-line ICI-based combination therapies for locally advanced or metastatic UC using phase 3 RCT data. In November 2023, three databases were searched for RCTs evaluating oncological outcomes in patients with locally advanced or metastatic UC who were treated with first-line ICI-based combination therapies. Network meta-analysis (NMA) was conducted to compare outcomes, including overall survival (OS), progression-free survival (PFS), objective response rates (ORRs), complete response rates (CRRs), and treatment-related adverse events (TRAEs). Subgroup analyses were based on PD-L1 status and cisplatin eligibility. The NMA included five RCTs. Enfortumab vedotin (EV) + pembrolizumab ranked the highest for improving OS (100%), PFS (100%), ORR (96%), and CRR (96%), followed by nivolumab + chemotherapy. EV + pembrolizumab combination superiority held across PD-L1 status and cisplatin eligibility. In patients who are cisplatin-eligible, EV + pembrolizumab significantly improved OS (HR: 0.68, 95%CI 0.47-0.99) and PFS (HR: 0.67, 95%CI 0.49-0.92) compared to nivolumab + chemotherapy. Durvalumab + tremelimumab was the safest combination for severe TRAEs, and EV + pembrolizumab ranked second. Our analyses support EV + pembrolizumab combination as a first-line treatment for locally advanced or metastatic UC. Thus, EV + pembrolizumab may become a guideline-changing standard treatment.
Keywords: Antineoplastic Combined Chemotherapy Protocols; lidé; Chemotherapy; karcinom z přechodných buněk; platina; Neoplasm Metastasis; humanizované monoklonální protilátky; protokoly protinádorové kombinované chemoterapie; nádory močového měchýře; Randomized Controlled Trials as Topic; Humans; Urinary Bladder Neoplasms; Immune Checkpoint Inhibitors; Platinum; Urothelial carcinoma; Enfortumab vedotin; Antibodies, Monoclonal, Humanized; Immune checkpoint inhibitors; Urologic Neoplasms; randomizované kontrolované studie jako téma; inhibitory kontrolních bodů; urologické nádory; Carcinoma, Transitional Cell; Metastasis; metastázy nádorů